To further incorporate computer-aided designs to improve preoperative planning in total hip arthroplasty: a cohort study - Cheng, Kai; Zhu, Haotian; Peng, Yuanhao; Yan, Han; Wen, Xinghua; Cheng, Zixuan; Ding, Huanwen (Frontiers in Surgery, 2024)
Background: Hip replacement surgeries are increasing in demand requiring rigorous improvements to a mature surgical protocol. Postoperative patient dissatisfaction mainly stem from postoperative complications mainly resulting from an inappropriate selection of prosthesis to complement the need of each patient. This results in prosthesis loosening, hospital-related fractures, postoperative complex pain which can all be attributed to inappropriate sizing. In this study we aim to further explore the intraoperative and postoperative benefits of incorporating computer aided design (CAD) in total hip arthroplasty (THA) preoperative planning.Methods: A total of 62 patients requiring total hip replacement surgery from 2021.1 to 2021.12 were collected and randomly divided into preoperative computer-aided simulated group and conventional X-ray interpretation group. Accuracy of implant size selection (femoral and acetabular implant) between the preoperative planning and surgical procedure of the two groups were compared. Patient parameters, perioperative Harris Hip Scores, operative time (skin-to-skin time), surgical blood loss and postoperative hospital stay were recorded and the differences between the two groups were statistically compared using a single sample t-test.All patients in the study were successfully operated and achieved good postoperative functional recovery. With CAD, the selection of the most suitable-sized prosthesis was more significantly more accurate when compared to the control group (accuracy of acetabular component between the CAD/control was 80.6%/61.3%, and the femoral component 83.9%/67.7%). Intraoperative blood loss (177.4ml/231.0ml, P=0.002), operation time (84.2±19.8min/100.3±25.9min, P=0.008), duration of hospital stay (6.5±3d/9.1±3.9d, P=0.003) and postoperative Harris Hip Score (81.9±6.5/74.7±11.1, P=0.003) were compared to the control group and showed statistical significance.Incorporating CAD into the preoperative planning of total hip arthroplasty can effectively guide the selection of the most suitable-sized prosthesis, effectively reducing intraoperative blood loss and promotes short-term functional recovery after THA.